NATIVE ENGLISH SPEAKER TEACHERS (NESTS) AND NON-NATIVE ENGLISH SPEAKER TEACHERS (NNESTS) IN INDONESIA: PREFERENCE AND DILEMMA - Septarini, Kartika (Jurnal Dinamika Pendidikan, 2014)
Issues about native English speaker teachers (NESTs) versus non-native English speaker teachers (NNESTs) have become a never ending debate. Whether native English speaker teachers or non-native English speaker teachers who are more appropriate to teach English in outer or expanding circle countries have been discussed and researched by some scholars. This paper discusses about peopleâs preference towards both of them by investigating previous research about peopleâs perception towards native English speaker teachers and non-native English speaker teachers. This paper also explores another issue arising from the dichotomy of native and non-native i.e. Whose English and what English should be taught in Indonesia. Whether English Native or other varieties of English is best taught in Indonesia.Keywords : Native English Teachers, Non-Native English Teachers, World Englishes